Upaya Peningkatan Kesadaran Akan Kebersihan Diri Pada Anak Di Desa Talapeta Kebupaten Deli Serdang - Gracia Sagita Silalahi; Tuti Atika (Universitas Maritim AMNI Semarang, 2024)
Health and hygiene are two things that cannot be separated. Every individual must be able to maintain their own hygiene in order to avoid various diseases that can arise due to lack of hygiene. Personal hygiene is a self-care effort carried out to maintain health both physically and psychologically. This personal hygiene must be applied starting from children, they must begin to be taught about the importance of maintaining personal hygiene from an early age so that it becomes a habit that continues into adulthood. This activity was carried out as one of the mini projects of Field Work Practice 2 activities carried out at Yayasan Fondasi Hidup (FH Indonesia) for the C-Prof program (Proyek Perlindungan dan Kesejahteraan Anak). The method used in this study is the Groupwork method with general stages (1) Preparation, (2) Assessment, (3) Alternative Program Planning, (4) Action Plan Formulation, (5) Program Implementation, (6) Evaluation and Results of Change and (7) Termination